Teacher support and student engagement: Correlation study on students of SMPN 4 Rengat Barat - Fitriyani, Eka; Gusripanto, Egi (Universitas Pendidikan Ganesha, 2021)
Students who are passive in learning, get bored easily, have no interest in lessons, and do not explore what is being learned are indications of low student engagement. Student engagement is student involvement in learning both in the academic and non-academic fields which can be seen through behavioral engagement, emotional engagement, and cognitive engagement. One of the factors that influence student engagement is the perception of teacher support. This study aims to determine the relationship between perceptions of teacher support and student engagement in students of SMPN 4 Rengat Barat. The research subjects were 146 students. Data collection used a scale of perceptions of teacher support and a scale of student engagement. Data analysis used Pearson product moment correlation using SPSS 23.0 for windows. The results of the data analysis showed that the hypothesis was accepted, there was a positive relationship between perceptions of teacher support and student engagement among students at SMPN 4 Rengat Barat. Obtained a correlation coefficient (r) of 0.456 and a correlation significance value of 0.000 (p <0.001), which means that the level of perceptions of teacher support was related to student engagement.